Determination of total phenolic content and antioxidant activity in pineapple fruit / Mohd Iszren Hairudin - Hairudin, Mohd Iszren (2010)
This study was conducted to evaluate and compare the total phenolic content and antioxidant activity of selected local pineapple fruit (Ananas Comosus). Three types of local pineapple cultivar (Josapine, Morris and N36) were analyzed for total phenolic content (TPC) and DPPH (l,l-Diphenyl-2-picrylhydrazyl) radical scavenging activities. The total phenolic content was measured by Folin-Ciocalteu's reagent while the antioxidant activity was estimated by using DPPH. It was found that Josapine contain the highest total phenolic content and the highest percentage free radical scavenging followed by Morris and N36. The total phenolic content for Josapine, Morris and N36 are 28.84±0.23 mg GAE/lOOg, 26.38±0.59 GAE/lOOg and 25.51±0.30 GAE/lOOg respectively. The three varieties of pineapple showed weak radical scavenging activity compared to Vitamin C. This study shows that for all three varieties of pineapple have weak antioxidant activities